Hábitos de higiene personal y el estado de salud en niños de la institución educativa inicial N°847 nuestra Señora de la Purísima, Punchana 2024 - Navarro Murayari, Mishell (2025)
The objective of this research study is to determine the level of personal hygiene habits and the health status of children at the Initial Educational Institution No. 847 Our Lady Of The Inmaculate 2024. The research used was relational and had a non-experimental design. The study population consisted of 100 children from the Initial Educational Institution N° 847 Our Lady Of The Inmaculate 2024. Observation was used to collect data, using an observation guide as an instrument. Validity was confirmed by three experts in the field. Reliability was assessed using item intercorrelation, with a Cronbach's alpha coefficient. After a pilot test, the Spearman coefficient of variation between personal hygiene habits and children's health status was 0.833, indicating a high positive correlation. Furthermore, the two tailed significance level is 0.05, which meets the established significance level (α = 0.05). This implies that there is sufficient statistical evidence to consider the relationship between the variables significant. In conclusion, the null hypothesis is rejected and the main hypothesis is accepted, which states that "the level of personal hygiene habits is significantly related to health status."